Supporting the transition to senior pediatric resident: An interactive online resource - Boschee, Erin; Walton, Jennifer; Foulds, Jessica; Forbes, Karen (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
Implication statementTransitions to roles with increasing clinical responsibility and independence can be anxiety provoking for many trainees. To support our pediatric residents preparing to transition from the role of junior to senior resident, we developed a novel asynchronous online interactive case-based resource. Our experience suggests that this resource was voluntarily utilized and can effectively increase trainee confidence and reduce anxiety about this key transitional stage. We suggest that interactive case-based resources can be utilized as supplemental support for residents preparing for residency transitions in other programs and settings.